Fuzzy Logic Aware QoS Multicasting in MANETs with Load Balance - Sirisala, Nageswara Rao; Bandi, Raswitha (International Journal of Engineering and Technology, 2018)
Mobile ad-hoc network (MANET) is a decentralized and infrastructure less network where a nodes can communicate with other nodes within the access region. Due to mobility node can enter and leave a network at any moment. Due to unstable nature of MANETs, the provision of Quality of Service (QoS) to the applications is a difficult task. In this paper, fuzzy logic enabled QoS multicast routing is proposed. Here energy, bandwidth and link expiry time are considered as a QoS parameters. The existing methods lost their performance in handling multi constrained QoS protocols, since defining the dynamic priorities among the multiple QoS parameters is not a trivial task. In the proposed method â€œFuzzy Logic Aware QoS Multicasting in MANETs with Load Balance-FQMLâ€, this issue is overcome by using fuzzy logic. The Competency Factor of each intermediate node along the route is calculated by aggregating itâ€™s QoS parameters using fuzzy inference system. In the classical multicast protocols, some of the nodes in the multicast tree are overloaded by having multiple branches towards the destination nodes. This leads to partition of the multicast tree and degrades the performance of protocols. In the proposed method, this problem is handled by limiting the number of branches at intermediate nodes. The results are taken in network simulator-ns2, where the proposed method could measure less number of path failures and improved results than existing methods.Â